The implementation of social responsiveness initiatives: case of Lithuania - Navickas, Valentinas; Kontautienė, Rima (Business: Theory and Practice, 2015)
A concept of social responsibility reflects public concerns and issues for a specific time, and these change with time. Various stakeholders as consumers, customers, employees, trade unions, communities, non-governmental organizations, foundations, donors, investors are more and more interested in the activities of companies (organizations), and influence on them in a variety of ways. Companies, for their part, also look for ways to meet the expectations of the public in the area of social responsibility. Corporate social responsiveness is an ability of business to respond to social pressure. The article analyzes the implementation of social responsiveness initiatives as organizational programs. Social responsiveness is understood as action dimension of corporate social responsibility. The paper deals with implementation of social responsiveness initiatives in Lithuania. Researched the socially responsiveness initiatives as organizational programs, the authors found that an active development of corporate social responsiveness positively influences on businesses and society relationship and contribute to sustainable development of region or country.